Therapy of rheumatic polymyalgia: the pathophysiologic management - M.A. Cimino; M.E. Secchi; M. Olivieri; M. Cutolo (PAGEPress Publications, 2011)
Polymyalgia rheumatica (PMR) is an inflammatory syndrome affecting older people whose prevalence has increased in recent years. The suppression of the hypothalamic-pituitary-adrenal axis (HPA) and ageing may contribute to the pathogenesis of PMR. Chronic stress (i.e. interpersonal, chronic infections etc.) in elderly people may represent a risk factor for the development of PMR. In fact, elderly represent per se a condition of endocrine senescence including adrenal hypofunction, in addition chronic stress represents a further harmful stimulus to seriously compromise endogenous glucocorticoid production. Synovitis and vasculitis characterize the majority of the patients. Serum cytokine and steroidal hormone patterns suggest that patients with PMR have an intensive inflammatory reaction. As a matter of fact, glucocorticoids represent the most useful temporary "replacement" treatment during the active phase of PMR. The use of modified-release glucocorticoids that might induce higher levels during the night (circadian rhythms as in physiological conditions), will represent another important approach to optimize PMR treatment and reduce the side effects. Combination therapy between glucocorticoids and inhibitors of pro-inflammatory cytokines should be tested in large studies and early cases of PMR.